Influence “Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan Pabrik Bulu Mata Palsu Di Desa Wirasana Kabupaten Purbalingga” - Priyanto, Rofik (Jurnal Kajian Ekonomi dan Manajemen Indonesia (JKEMI), 2023)
This research aims to determine the effect of compensation and work discipline on the work productivity of employees of the False Eyelash Factory in Wirasana Village, Purbalingga Regency. Wirasana Village is a center for wig crafts in Purbalingga Regency. The wig industry is divided into two types based on the materials used, namely synthetic hair crafts and real hair crafts. There are at least 8 production units that manage production goods made from synthetic hair, the results of synthetic hair crafts include buns, wigs, Balinese fir, hair extensions, and so on. This research uses quantitative methods which function to research certain populations or samples, data collection uses research instruments, statistical data analysis. The data collection method is a questionnaire to obtain primary data, while secondary data is obtained from documentation. The results of this research show that the compensation variable has a positive and significant effect on work productivity for employees who work at BKM Jaya, Wirasana Village, Purbalingga Regency. This means that if the compensation variable is increased, work discipline will increase, assuming the work productivity variable is constant. The work discipline variable has a positive and insignificant effect on work productivity. This means that if work discipline is improved, compensation will increase, assuming the work productivity variable is constant